Valores-notícia no jornalismo cultural regional: o caso do programa Diversidade - Araújo, Saulo Queiroz de (2021)
This research set out to investigate the criteria of news called news-values by journalism theorists from the analysis of a daily cultural newscast, “Diversidade”, produced and shown by TV Itararé (affiliated with TV Cultura in Campina Grande-PB). The objective was to understand how these elements of selection of guidelines are applied in the context of the production of cultural journalism of proximity, having as scope the main concepts that gave theoretical support to the investigation: public communication as an area in which the production of content implies in social, cultural and educational responsibilities; cultural journalism understood as a thematic and singular segment in the macro field of journalism; and news values as factors applied to journalistic routines during the news selection. The methodology applied to the research was content analysis in a case study with participant observation, resulting in the collection of data that led us to identify in the team's routines the non-systematic application of news values in the production of the analyzed program and media inclusion as unprecedented news value.